Developing IT-assisted Adversity Response Profile for Lectures Online during New Normal - Ardiansyah, Adi Satrio; Sari, Salsabilla Naura; Caesario, Nico (Universitas Negeri Semarang, 2021)
Purpose: The purpose of this study was to develop valid and reliable IT-assisted ARP in online lectures during New Normal. IT - assisted ARP Product is the innovative learning instruments that was develop to help educators in understanding the problems experienced by students, so that they can maximize the implementation of distance education.Â Methods: The research method used was Research and Development (RD) which was conducted on 50 students of the Department of Mathematics, Universitas Negeri Semarang. This development research consists of three stages, namely the initial investigation, the prototype phase and the assessment phase which will then be analyzed using quantitative analysis techniques.Â Result: The results showed that the IT-ASSISTED ARP met the valid and reliable criteria with the rehabilitee value is very high, namely 0, 98.Â Novelty: With the discover of valid and reliable ARP, educators can use it to determine the level of student ability in dealing with learning problems during the New Normal.